S97 Neutrophil epigenetic signatures in the context of acute respiratory distress syndrome. (11th November 2022) - Xu, X; Sadiku, P; Griffith, D; Sanchez-Garcia, MA; Walmsley, SR
Abstract : Introduction: Neutrophils drive acute respiratory distress syndrome (ARDS) pathogenesis, which is characterised by profound hypoxia. Hypoxia exposure acutely alters neutrophils metabolisms and functions. 1 Hypoxic reprogramming of chromatin accessibility has previously been reported in other cell types. 2 We questioned whether blood neutrophils from patients with systemic hypoxaemia in the context of ARDS had evidence of altered expression of histone modification enzymes and regulatory proteins. Methods: Peripheral blood neutrophils of patients meeting the Berlin Definition of ARDS were studied acutely (n = 13), alongside samples from age-and-sex matched healthy volunteers (n = 4). Histone modification enzymes and accessory proteins were measured by high-performance liquid chromatography-mass spectrometry. Results: ARDS blood neutrophils acutely altered the abundances of histone modifying enzymes and regulatory proteins impacting histone 3 lysine 4, 9, 27 methylation and histone 3 lysine 27 acetylation. We observed increased abundances of components of complex proteins associated with SET1 (COMPASS), switch/sucrose non-fermentable (SWI/SNF) chromatin remodelling complex, polycomb repressive complex 2 (PRC2), C-terminal binding protein complex (CtBP), corepressor for element-1-silencing transcription factor complex (CoREST), nucleosome remodelling and deacetylation complex (NuRD) and transcriptional repressor complex mSin3A. Conclusions: Blood neutrophils isolated from patients with ARDS demonstrated altered expression of enzymes important for histone modifications. Future work is required to understand whether there are longer term consequences to these changes in enzyme expression for key neutrophil effector functions that are consequent upon systemic hypoxaemia. References: Thompson AAR, Dickinson RS, Murphy F, Thomson JP, Marriott HM, Tavares A, et al . Hypoxia determines survival outcomes of bacterial infection through HIF-1 alpha-dependent reprogramming of leukocyte metabolism. Science Immunology 2017;2 (8):12. Batie M, Frost J, Frost M, Wilson JW, Schofield P, Rocha S. Hypoxia induces rapid changes to histone methylation and reprograms chromatin. Science 2019;363 (6432):1222–6.